2014
DOI: 10.1121/1.4869255
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin changes in whistle structure with watercraft activity depends on their behavioral state

Abstract: Dolphins rely on whistles to identify each other and to receive and convey information about their environment. Although capable of adjusting these signals with changing environments, there is little information on how dolphins acoustically respond to different watercraft activities and if this response depends on dolphin behavioral state. Bottlenose dolphin whistles were recorded in the presence of research and dolphin-watching boats. Dolphins emitted lower frequency and longer whistles when interacting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…The influence of the behavioral context, social and foraging, on the whistle structure was independent of the population. Accordingly, a similar frequency shift in whistles was detected during the behavioral states characterized by a high level of arousal (Acevedo‐Gutièrrez & Stienessen, ; Hawkins, ; King & Janik, ; La Manna et al, ; May‐Collado & Quiñones‐Lebrón, ; Rako‐Gospić & Picciulin, ). Moreover, duration, number of inflection points, and frequency range decreased with the increasing group size, independently of the population (PC2), even if data for group size between 25 and 35 individuals were lacking.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The influence of the behavioral context, social and foraging, on the whistle structure was independent of the population. Accordingly, a similar frequency shift in whistles was detected during the behavioral states characterized by a high level of arousal (Acevedo‐Gutièrrez & Stienessen, ; Hawkins, ; King & Janik, ; La Manna et al, ; May‐Collado & Quiñones‐Lebrón, ; Rako‐Gospić & Picciulin, ). Moreover, duration, number of inflection points, and frequency range decreased with the increasing group size, independently of the population (PC2), even if data for group size between 25 and 35 individuals were lacking.…”
Section: Discussionmentioning
confidence: 59%
“…The bottlenose dolphin, Tursiops spp., live in complex fission–fusion societies (Connor, Wells, Mann, & Read, ; Mann, Connor, Barre, & Heithaus, ) and have developed frequency‐modulated, narrow‐band signals, called whistles, used for individual recognition, contact maintenance, and group coordination (Janik & Sayigh, ; MacFarlane et al, ). Many studies have found acoustic variation between different populations of bottlenose dolphin (Azevedo et al, ; Hawkins, ; Jones & Sayigh, ; La Manna, Rako‐Gospić, Manghi, Picciulin, & Sarà, ; May‐Collado & Wartzok, ; Morisaka et al, ; Papale et al, ; Wang et al, ), but understanding such variations without disentangling the concurrent effects of different factors shaping dolphin acoustic behavior may be limiting and frustrating (Gridley, Elwen, Rashley, Badenas Krakauer, & Heiler, ; Heiler, Elwen, Kriesell, & Gridley, ; May‐Collado & Quiñones‐Lebrón, ; Sayingh, ). Because the soundscape of a given environment may change over time, variations in dolphin whistles may be the response to varying background noise levels, for example, to facilitate signal transmission and have an effective communication (Ansmann et al, ; May‐Collado & Wartzok, ; Papale, Gamba, Perez‐Gil, Martin, & Giacoma, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have investigated the likely impact of boat presence on dolphin communication signals including whistles (Buckstaff, 2004;May-Collado & Quiñones-Lebrón, 2014;Scarpaci et al, 2000), few have controlled for other key covariates that may influence whistle parameters such as behavioural context (Lemon, Lynch, Cato, & Harcourt, 5 2006;May-Collado & Quiñones-Lebrón, 2014;Scarpaci et al, 2000). Furthermore, although variation in acoustic parameters can relate to behavioural state (Azevedo et al, 2010;MayCollado, 2013) and may be useful in predicting surface behaviour (Henderson, Hildebrand, & Smith, 2011;Henderson, Hildebrand, Smith, & Falcone, 2012;Hernandez, Solangi, & Kuczaj, 2010) the available information poorly explains the causative factors of this variability.…”
mentioning
confidence: 99%
“…2004; Morisaka et al, 2005;Guerra et al, 2014;May-Collado and Quiñones-Lebrón, 2014;Heiler et al, 2016). Furthermore, different dolphin populations also appear to vary in the source levels of the whistles they produce (Jensen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%